Influence of Intermittent Submerged Breakwater on the Hydrodynamic Impacts of Infragravity Waves on Fringing Reef - Yu Renshi; Qu Ke; Nie Wenjun (Redai dili)
Coral reef systems are vital natural barriers that dissipate wave energy and protect coastlines. However, anthropogenic damage has severely compromised this protective function, necessitating restoration efforts such as submerged breakwaters. To understand the influence of discontinuous submerged breakwaters on wave hydrodynamics over reef flats, this study employed physical model experiments and numerical simulations. A series of irregular waves were tested under scenarios with and without a breakwater, systematically varying the key parameters: significant wave height, water depth over the breakwater crown, spectral peak period, and gap width. The results demonstrate that discontinuous submerged breakwaters reduce the hydrodynamic loads on reef flats by generating wave reflection and refraction, as well as by enhancing the viscous dissipation of rip currents at discontinuities with incident waves. Specifically, breakwaters reduce the infragravity wave energy and wave heights, wave-induced set-up on the reef flat, and maximum wave run-up on the back reef slope. The reduction in wave run-up and reef flat set-up is most significant under minimal significant wave height conditions. Increasing the water depth over the breakwater crown can lead to incomplete wave breaking, thereby causing a relative increase in the contribution of short waves to the total wave run-up. Increasing the gap width enhances the effectiveness of the breakwater in reducing both the run-up and set-up, while simultaneously weakening the resonance amplification of infragravity waves on the reef flat. Conversely, increasing the spectral peak period intensifies infragravity wave resonance. Finally, the complex hydrodynamics along the reef are revealed using the waves2Foam model in OpenFOAM to construct a three-dimensional numerical wave flume. The study found that abrupt rip currents are generated at the discontinuities of submerged breakwaters while simultaneously reducing the onshore flow velocity over the reef flat. In conclusion, discontinuous submerged breakwaters are a viable engineering measure for mitigating coastal hazards in degraded reefs by reducing damage to infragravity waves, wave set-ups, and wave run-ups. These findings provide essential mechanistic insights and quantitative guidance for designing effective reef restoration and protection structures that incorporate submerged breakwaters.